(untitled) (American Journal of Islam and Society, 1993)
This is a "work in progress" presentation based on mearch I am now conducting about the development of Islamic political philosophy during the classical period of Islam. My contention is that a better understanding of that tradition puts the current debate about Islamic fundamentalism or resurgence into a new perspective. Behind the sensational, popular demands for greater adherence to the strictures of the revealed law of Islam lies an issue of fundamental importance: how divine revelation is to be understd and interpreted for political guidance. Those who developed Islamic political philosophy spoke directly to this issue and did so in a manner that merits the attention of contemporary Muslim activists, scholars interested in Islam, and thoughtful human beings in general. They thought clearly about the relationship between religious belief and political practice because they addressed the issue ditectly and without preconceptions. Consequently, whatever our religious and cultural origins, we can benefit greatly from their teaching. One of my goals is to refocus current social science scholarship while engaging Muslim scholars in debate on topics they deem urgent. Lately, there have been many, perhaps too many, reports and prognostics concerning the success of resurgent Islam as well as the challenges it poses to Middle Eastern and western regimes. Such studies invariably talk about, rather than with, those calling for greater attention to Islamic precepts and practices; they presuppose and reinforce an attitude of "us" and "our valued’ vetSUS "them" and "their values." Such a posture not only fosters antagonism and misunderstanding, it also ignores the way Muslims are now addressing this complex phenomenon. Indeed, for almost a decade, Muslims trained in the West have been investigating how western learning, especially the social sciences, illuminates traditional Islamic sciences and vice versa. This task addresses, at the highest level, the issue behind the call for application of the Shari’ah and offers the best Contemporary possibility of achieving some kind of intercultural understanding. It offers those interested in western and Islamic culture a unique opportunity to delve mare deeply into another culture and thereby understand the other and their own culture better. Another goal is to investigate how philosophers within the classical period of Islam understood revelation and its outward manifestationprophecy- to influence political life. While mast scholars recognize the ...